Characteristics of sow milks at different lactation stages and their frozen storage stabilities. (June 2021) - Ren, Cuirong; Jin, Qingzhe; Jin, Jun; Zhang, Yanbing; Wang, Xingguo
Abstract: Characteristics of sow milk fats at different lactation stages, including colostrum (on day-1 of lactation) and milk (on day-15 of lactation), were systematically investigated from the emulsions, milk fat globules (MFGs) to fats. The viscosities of sow milks were significantly influenced by different lactation stages, in which colostrum showed a higher viscosity than milk. Colostrum fat globules had a lower volume-weighted average diameter (D43 ) (4.03 ± 0.21 μm), surface-weighted average diameter (D32 ) (2.05 ± 0.13 μm) and higher absolute zeta-potential (10.09 ± 0.09 mV) than those of milk. The unsaturated ratios of MFGs in sow milk were reduced with the increasing size of the globules, resulting in that colostrum fat had a lower melting temperature of 30.26 ± 0.98 °C with a corresponding lower starting crystallization temperature of 7.38 ± 0.55 °C compared with milk fat. The general stability of sow milk during storage could be reflected from the moisture distributions: bound water showed an overall downward trend; while a downtrend of free water was found during frozen storage at −20 °C for 4 months. These results establish the foundations for the improvement and development of sow milk substitutes, as well as for the feasibility of being a substitute for human milk. Highlights: Sow milks and their fats at different lactation stages were characterized. Colostrum showed higher viscosity and smaller globule size compared to milk. Raman spectra is an effective method for monitoring sow milk fat globules (MFGs). Sow milk fat globules tended to aggregate as frozen storage time prolonged. Sow milk fat showed excellent melting behavior for both food and feeding purposes.